2016
DOI: 10.1017/s0047279416000623
|View full text |Cite
|
Sign up to set email alerts
|

Do Personal Budgets Increase the Risk of Abuse? Evidence from English National Data

Abstract: With the continued implementation of the personalisation policy, Personal Budgets (PBs) have moved to the mainstream in adult social care in England. The relationship between the policy goals of personalisation and safeguarding is contentious. Some have argued that PBs have the potential to empower recipients, while others believe PBs, especially Direct Payments, might increase the risk of abuse.This paper provides empirical evidence about levels of uptake of PBs and safeguarding referrals in England based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Specifically, detailed notes were made on the findings and conclusions presented in each article, study, or report; these notes were then examined to ascertain perennial themes or topics of interest. As Table demonstrates, a variety of themes emerged; for instance, several articles discussed how DF might exacerbate or reduce risks for older people (Carr & Robbins, ; Ismail et al, ; Mitchell, Baxter, & Glendinning, ), explored the cost‐effectiveness of DF programs (Jones & Netten, ; Rummery, Bell, Bowes, Dawson, & Roberts, ; Woolham & Benton, ), and highlighted some of the organisational challenges associated with the implementation of DF programs by various health authorities (Doty, Mahoney, & Sciegaj, ; Duffy, ; Gill et al, ; Velzke, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, detailed notes were made on the findings and conclusions presented in each article, study, or report; these notes were then examined to ascertain perennial themes or topics of interest. As Table demonstrates, a variety of themes emerged; for instance, several articles discussed how DF might exacerbate or reduce risks for older people (Carr & Robbins, ; Ismail et al, ; Mitchell, Baxter, & Glendinning, ), explored the cost‐effectiveness of DF programs (Jones & Netten, ; Rummery, Bell, Bowes, Dawson, & Roberts, ; Woolham & Benton, ), and highlighted some of the organisational challenges associated with the implementation of DF programs by various health authorities (Doty, Mahoney, & Sciegaj, ; Duffy, ; Gill et al, ; Velzke, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…For example, the article mentions that depending on the structure of the particular DF program, the amount of choice and responsibility offered to consumers will vary (ibid., p. 47), although they do not elaborate on the consequences of this variation. Ismail et al () nod to some of the possible consequences of increased choice for safeguarding, noting that “on a conceptual level, the link between increased choice and control through [DF] and better safeguarding outcomes does not seem to hold true” (p. 307). The authors do not present further analyses that contribute to understanding better the relation between increased choice and user risk.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have explored the dynamics of PA/employer relationships (Graham, 2015;Shakespeare, Stöckl, & Porter, 2018) and PA characteristics (Skills for Care, 2017). Risks such as neglect, exploitation or misuse of public funds have been weighed against the advantages articulated of choice for people using care services and their empowerment (Ismail et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…International reports found little evidence of heightened risk to consumers in self‐management programs. Two English studies found that adverse events did occur, however, their prevalence was no higher than in agency‐managed programs (Ismail et al., 2017; Manthorpe & Samsi, 2013). The authors cautioned against imposing safeguards that would infantilise older consumers and stifle their agency and self‐determination.…”
Section: Introductionmentioning
confidence: 99%